Determination of ion recombination and polarity effects for the PTW Advanced Markus ionization chamber in synchrotron based scanned proton and carbon ion beams. (April 2022) - Mirandola, A.; Maestri, D.; Magro, G.; Mastella, E.; Molinelli, S.; Rossi, E.; Russo, S.; Vai, A.; Ciocca, M.
Highlights: Ion recombination, polarity and charge multiplication effect. Carbon ions radiotherapy. High dose per fraction proton eye treatments. Dosimetry with small-gap plane-parallel ionization chamber. Abstract: The aim of this work was the investigation of the ion recombination and polarity factors ( ksat ad kpol ) for a PTW Advanced Markus ionization chamber exposed to proton and carbon ion beams at the Centro Nazionale di Adroterapia Oncologica. Measurements with protons were specifically dedicated for ocular treatments, in the low energy range and for small, collimated scanning fields. For both protons and carbon ions, several measurements were performed by delivering a 2D single energy layer of 3x3 cm 2 and homogeneous, biologically-optimized SOBPs. Data were collected at different depths in water, by varying the voltage values of the ionization chamber and for two different dose rates (the nominal one and one reduced to 20% of it). The ksat -values were determined from extrapolation of the saturation curves. Furthermore kpol -values were calculated using the recommendations from the International Atomic Energy Agency (IAEA) Technical Report Series (TRS)-398 Code of Practice. Results showed that the Advanced Markus performs optimally in this clinical scenario characterized by small treatment volumes and high dose gradients although for both particle types, but particularly for carbon ions, a charge multiplication effect up to 1.7% occurs at voltage higher than 150 V. For protons, both the ion recombination and polarity corrections were always smaller than 0.3%, for all the analysed cases and adopted dose rates, so not affecting the dosimetric measurements for clinical routine. For carbon ions the polarity effect can be neglected while ion recombination has to be carefully calculated and cannot be neglected since corrections even higher than 1% can be found, especially at high LET measuring points.